The distribution of new HIV infections by mode of exposure in Morocco. (14th February 2013) - Mumtaz, Ghina R; Kouyoumjian, Silva P; Hilmi, Nahla; Zidouh, Ahmed; Rhilani, Houssine El; Alami, Kamal; Bennani, Aziza; Gouws, Eleanor; Ghys, Peter Denis; Abu-Raddad, Laith J
Abstract : Objectives: Building on a wealth of new empirical data, the objective of this study was to estimate the distribution of new HIV infections in Morocco by mode of exposure using the modes of transmission (MoT) mathematical model. Methods: The MoT model was implemented within a collaboration with the Morocco Ministry of Health and the Joint United Nations Programme on HIV/AIDS. The model was parameterised through a comprehensive review and synthesis of HIV and risk behaviour data in Morocco, mainly through the Middle East and North Africa HIV/AIDS Synthesis Project. Uncertainty analyses were used to assess the reliability of and uncertainty around our calculated estimates. Results: Female sex workers (FSWs), clients of FSWs, men who have sex with men (MSM) and injecting drug users (IDUs) contributed 14%, 24%, 14% and 7% of new HIV infections, respectively. Two-thirds (67%) of new HIV infections occurred among FSWs, clients of FSWs, MSM and IDUs, or among the stable sexual partners of these populations. Casual heterosexual sex contributed 7% of HIV infections. More than half (52%) of HIV incidence is among females, but 71% of these infections are due to an infected spouse. The vast majority of HIV infections among men (89%) are due to high-risk behaviour. A very small HIV incidence is predicted to arise from medical injections or blood transfusions (0.1%). Conclusions: The HIV epidemic in Morocco is driven by HIV incidence in high-risk population groups, with commercial heterosexual sex being the largest contributor to incidence. There is a need to focus HIV response more on these populations, mainly through proactive and sustainable HIV surveillance, and the expansion and increased geographical coverage of services such as condom promotion among FSWs, voluntary counselling and testing, harm reduction and treatment.